An Analysis of Immunoreactive Signatures in Early Stage Hepatocellular Carcinoma - Yu Hong; Jiang Long; Hai Li; Shuhong Chen; Qiqi Liu; Bei Zhang; Xiaomin He; Yan Wang; Hongyi Li; Yimei Li; Tao Zhang; Chenzhen Lu; et al. (EBioMedicine, 2015)
Background: Hepatocellular carcinoma (HCC) is prevalent worldwide and early diagnosis of HCC is critical for effective treatment and optimal prognosis. Methods: Serum was screened first by immunoproteomic analysis for HCC-related tumor associated antigens (TAAs). Selected TAAs were clinically evaluated retrospectively in patients with HCC, liver cirrhosis, chronic hepatitis and healthy controls. Levels of autoantibody to the selected TAAs were measured by protein microarrays containing protein antigens of the candidate TAAs. Analyses were done by using receiver operating characteristics (ROC) to calculate diagnostic accuracy. Findings: Twenty-two candidate TAAs were assessed by protein microarray analysis in 914 participants with serum α-fetoprotein (AFP) available. Twelve candidate TAAs were statistically different in signal intensity between HCC and controls. Among them, CENPF, HSP60 and IMP-2 showed AUC (area under the curve) values of 0.826, 0.764 and 0.796 respectively for early HCC. The highest prevalence of autoantibody positivity was observed in HCC cases with BCLC tumor stage A, well-differentiated histology and Child-Pugh grade C. Specifically, 73.6% or 79.3% cases of early HCC with negative AFP were positive for autoantibody to CENPF or HSP60. Interpretation: Tumor-associated autoimmune reactions may be triggered by early stage HCCs. Measurement of serum autoantibody to TAAs may be complementary to AFP measurements and improve diagnosis of early HCC.